The value of ISE: main studies and investor perspective - Macedo, Fernanda (2012)
This study has been prepared with the aim of bringing together the main research lines that seek to identify and convey the value of participating in initiatives like the ISE. This document is structured on three major fronts. On the first front, we conducted a survey to collect the main data on SRI trends in the two largest market niches: Europe and the United States, besides results from an MIT research study conducted among executives on the value of sustainability in the current market. Next, we carried out a non-exhaustive survey on academic studies that seek to identify the intangible and tangible gains achieved by companies through their participation in the ISE or related initiatives. Finally, we present the results of a survey done with major Brazilian pension funds aimed at investigating the knowledge of the ISE and how it could be used in their analysis and decision-making process.